2015
DOI: 10.1177/1753193415601055
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic antibiotics in open distal phalanx fractures: systematic review and meta-analysis

Abstract: A systematic review was conducted on 30 December 2014 to determine whether prophylactic antibiotics reduce the risk of superficial infection and osteomyelitis following open distal phalanx fractures. Four randomized controlled trials (353 fractures) were suitable for meta-analysis. There was no statistically significant difference between rates of superficial infection in the two groups. This finding persisted when only the two most recent and highest quality trials were included. There were no reported cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 22 publications
(44 reference statements)
2
14
1
Order By: Relevance
“…First, the provision of preoperative antibiotics (either as a short oral course in the days leading up to emergency surgery or as a one-off dose at the time of anaesthesia induction) was not associated with a reduced risk of SSI in either the elective or emergency surgery models. This is in keeping with the wider literature on perioperative antibiotic use in upper limb surgery 34 , 35 , 44 , 45 which demonstrates no benefit from (pre- or postoperative) antibiotics in patients who have no clinical features of infection and who are destined for surgery. As we approach an existential crisis surrounding antimicrobial resistance 25 , surgeons could consider exercising greater restraint and prescribe fewer antibiotics until definitive evidence from high-quality multicentre randomised trials is generated.…”
Section: Discussionsupporting
confidence: 79%
“…First, the provision of preoperative antibiotics (either as a short oral course in the days leading up to emergency surgery or as a one-off dose at the time of anaesthesia induction) was not associated with a reduced risk of SSI in either the elective or emergency surgery models. This is in keeping with the wider literature on perioperative antibiotic use in upper limb surgery 34 , 35 , 44 , 45 which demonstrates no benefit from (pre- or postoperative) antibiotics in patients who have no clinical features of infection and who are destined for surgery. As we approach an existential crisis surrounding antimicrobial resistance 25 , surgeons could consider exercising greater restraint and prescribe fewer antibiotics until definitive evidence from high-quality multicentre randomised trials is generated.…”
Section: Discussionsupporting
confidence: 79%
“…Although favorable results can be achieved with surgical treatment of closed distal phalangeal fractures, complications such as infection, reduction loss, nonunion, or complex regional pain syndrome can occur in selected patients. [23][24][25] However, none of these complications were observed in any of the patients in this study.…”
Section: Discussioncontrasting
confidence: 48%
“…Most isolated metacarpal fractures can be treated using nonoperative interventions. Relevant cadaveric studies have reported that every 2 mm of shortening would result in approximately 7° of extensor lag [ 16 , 17 ]. Because most phalangeal joints hyperextend by approximately 20°, the metacarpophalangeal joints can still remain neutral even when the metacarpus is shortened 5 to 6 mm.…”
Section: Discussionmentioning
confidence: 99%